A polemical discourse over the legitimation of illegitimate children under Islamic Law - Sarumi, Isa Abdur-Razak; Mohd, Azizah; Ibrahim, Norliah (IIUM Press, 2019)
Muslim jurists unanimously agree that any woman that gives birth to a child, be it a married or slave-woman, the child is to be attributed to her husband or her proprietor, and legitimacy of that child is to be established except the child is disclaimed by the husband through imprecation (li’an). However, dissension over the legitimation of children born out of wedlock has long been recorded in the classical books of Islamic Jurisprudence, although the majority of jurists’ opinion secured an overwhelming preponderance over others. The argument over the legitimation has recently been advanced in order to find a feasible solution to the alarming condition of children born out of wedlock. Interestingly, both opponents and proponents of the legitimation of illegitimate children among Muslim scholars buttress their arguments with the famously narrated hadith “al-walad lil firash” (“The child is traced to the owner of the bed (i.e. the legitimate husband).” on the subject matter. Therefore, this article seeks to explore juristic interpretations of the hadith and the rationale behind the scholars’ dissention. This article is a result of a research that has been done through the adoption of a qualitative approach of research, which includes doctrinal and non-doctrinal legal research methodologies. It has been found that attributing a child to his putative father after the acknowledgement does not contravene the fundamental principle of Shariah; it is rather an opinion held by the majority of contemporary Muslim scholars.